Contraction-mapping algorithm for the equilibrium problem over the fixed point set of a nonexpansive semigroup - Hai, Trinh Ngoc; Thuy, Le Qung (Mathematical modelling and analysis, 2019)
In this paper, we consider the proximal mapping of a bifunction. Under the Lipschitz-type and the strong monotonicity conditions, we prove that the proximal mapping is contractive. Based on this result, we construct an iterative process for solving the equilibrium problem over the fixed point sets of a nonexpansive semigroup and prove a weak convergence theorem for this algorithm. Also, some preliminary numerical experiments and comparisons are presented. First Published Online: 21 Nov 2018